Development and research of the circuit for measuring the leakage current when testing the insulation with the higher rectified voltage - R. T. Khazieva; A. N. Mukhametshin (Известия высших учебных заведений: Проблемы энергетики)
OBJECT. When developing DC test voltage sources to assess the insulation quality of high-voltage equipment, the task is to measure the leakage current flowing through the test object. METHODS. When solving the problem the authors proposed a technical solution for measuring the current flowing through the test when testing insulation with rectified voltage, which uses a precision resistor, an isolating amplifier, a 2-channel operational amplifier with a unipolar power supply, zero voltage drift, and an ADC of a microcontroller.RESULTS. The article in the course of the study of the stand of the circuit for measuring the leakage current flowing through the tested object when testing the insulation with rectified voltage, an experimental industrial sample was created, which makes it possible to measure the leakage current value in the range from 10 μA to 1000 μA. The use of the developed circuit for measuring the current flowing through the test object when testing the insulation with rectified voltage makes it possible to calculate the DC component of the voltage signal from the alternating signal and in real time, and, therefore, to quickly monitor the current in high-voltage circuits for continuous monitoring. CONCLUSION. So the introduction of this sample will make it possible, on its basis, to create a number of digital measuring microammeters that make it possible to measure the leak-age current in high-voltage test installations for testing the insulation of objects from 15 nF to 200 nF, in the leakage current measurement range from 10 μA to 1000 μA. The results obtained can be used in high voltage technology to study circuits for measuring the leakage current flowing through the test object when testing insulation with rectified voltage.